2008
DOI: 10.1148/radiol.2463070390
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Laser Ablation for Hepatocellular Carcinoma: A Multicenter Study

Abstract: Percutaneous LA may be considered a safe treatment for small HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 29 publications
0
38
2
Order By: Relevance
“…In this group, 32 (61.44%) of 52 lesions treated were considered a therapeutic success. This apparently unsatisfactory result is in contrast with the data reported by various publications [9,15], and also with the results reported elsewhere by the same authors [16]: this seems to rule out an inadequate skill of the operators as a possible cause of the low success rate. Another reason for the discrepancy concerns the localization of the lesions: the more they are strictly in contact with risk structures, the more likely an incomplete necrosis after a percutaneous approach is to be expected.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In this group, 32 (61.44%) of 52 lesions treated were considered a therapeutic success. This apparently unsatisfactory result is in contrast with the data reported by various publications [9,15], and also with the results reported elsewhere by the same authors [16]: this seems to rule out an inadequate skill of the operators as a possible cause of the low success rate. Another reason for the discrepancy concerns the localization of the lesions: the more they are strictly in contact with risk structures, the more likely an incomplete necrosis after a percutaneous approach is to be expected.…”
Section: Discussioncontrasting
confidence: 68%
“…In a larger series, the same authors [16] reported a complete necrosis rate of 81.14% in 314 HCC nodules (diameter ≤3 cm) ( Table 3). We think this discrepancy can be explained just by analyzing the selection criteria of the nodules.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A complete response rate of 78% was observed following laser ablation in a study of 432 patients, while the local recurrence rate was found to be 20%, with 3-and 5-year survival rates as high as 61% and 34% respectively [48][49][50] . The safety of laser ablation has also been found to be comparable with other percutaneous modalities like RFA with major and minor complication rates of 1.5% and 6.2% respectively, and a mortality rate of 0.8% as reported by an Italian study [51] . While these results may be encouraging, they do not provide evidence of greater efficacy or a better safety profile over alternate technology that is available at a much cheaper cost and hence, much more readily than percutaneous laser ablation [52] .…”
Section: Laser Ablationmentioning
confidence: 54%